Velocity distributions in vegetated particle-laden flows - Tay, Ming Li. (2011)
The existence of vegetation in open channels has several influences over fluvial processes, such as increasing resistance to flow, or causing higher sediment deposition rates. This causes the flow structure to be different from non-vegetated flow.This project was carried out in the Hydraulics Modeling Laboratory within Nanyang Technological University, and an open channel flow was modelled using a 12m long, 0.3m wide and 0.45m deep flume. Vegetation was modelled using rigid cylindrical rods. A total of 4 configurations were used, named as Cases A30, A60, B60 and C60, based on the distance between them as well as the diameter of rods that were used. The aim was to determine the flow velocity profile concentration that each individual case would have, and comparisons were made between them. The results were analysed and it was shown that the existence of vegetation created some resistance to flow, lowering the flow velocity. The presence of the vegetation also created sand dune formations due to the increased resistance to flow, and such occurrence was dependent on the vegetation density and flow velocity.